‘This Isn’t My Expectation’: Excel in Auditing - Irafahmi, Diana Tien; Williams, P John (Asian Journal of Business and Accounting, 2021)
ABSTRACT Manuscript type: Research paper Research aims: This study examines the perceptions of undergraduate accounting students about the use of Excel in an auditing course. Design/Methodology/Approach: A qualitative interview design is employed in this study. A total of 20 participants shared their perceptions in three group interviews. Their statements were analysed using thematic analysis. Research findings: Themes of agility and undesirability appeared central to the experience of Excel usage in auditing. The agility theme refers to students’ rapid adaptation to the use of Excel for auditing purposes. The undesirability theme deals with students’ expectations of using software beyond Excel. Theoretical contribution/Originality: This study generated an understanding of expectations around technology from the perspective of accounting students, which is rarely examined. For students, the future of the accounting and auditing profession relies on up-to-date technologies, and universities should provide experiences in accessing and learning to use such technologies in accounting education. Practitioner/Policy implications: The findings of this study provide an understanding for accounting educators and higher education institutions about the expectations of students related to the type of technology that must be covered in accounting curricula. Research limitations: This study collected data from only one public university in Indonesia. Students’ perceptions in this institution may not be the same as those in other institutions. Caution must be taken when generalising and interpreting the findings to other institutions. Keywords: Accounting Education, Auditing, Excel, Technological Competence, Undergraduate JEL Classification: M41, M42, A22